Combinatorial Analysis - 26.6 Other Lattice Path Numbers

From testwiki
Revision as of 17:47, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
26.6.E5 m , n = 0 D ( m , n ) x m y n = 1 1 - x - y - x y superscript subscript 𝑚 𝑛 0 𝐷 𝑚 𝑛 superscript 𝑥 𝑚 superscript 𝑦 𝑛 1 1 𝑥 𝑦 𝑥 𝑦 {\displaystyle{\displaystyle\sum_{m,n=0}^{\infty}D(m,n)x^{m}y^{n}=\frac{1}{1-x% -y-xy}}}
\sum_{m,n=0}^{\infty}D(m,n)x^{m}y^{n} = \frac{1}{1-x-y-xy}

sum(sum((sum(binomial(n,k)*binomial(m + n - k,n), k = 0..n))*(x)^(m)* (y)^(n), n = 0..infinity), m = 0..infinity) = (1)/(1 - x - y - x*y)
Sum[Sum[(Sum[Binomial[n,k]*Binomial[m + n - k,n], {k, 0, n}, GenerateConditions->None])*(x)^(m)* (y)^(n), {n, 0, Infinity}, GenerateConditions->None], {m, 0, Infinity}, GenerateConditions->None] == Divide[1,1 - x - y - x*y]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E6 n = 0 D ( n , n ) x n = 1 1 - 6 x + x 2 superscript subscript 𝑛 0 𝐷 𝑛 𝑛 superscript 𝑥 𝑛 1 1 6 𝑥 superscript 𝑥 2 {\displaystyle{\displaystyle\sum_{n=0}^{\infty}D(n,n)x^{n}=\frac{1}{\sqrt{1-6x% +x^{2}}}}}
\sum_{n=0}^{\infty}D(n,n)x^{n} = \frac{1}{\sqrt{1-6x+x^{2}}}

sum(D(n , n)* (x)^(n), n = 0..infinity) = (1)/(sqrt(1 - 6*x + (x)^(2)))
Sum[D[n , n]* (x)^(n), {n, 0, Infinity}, GenerateConditions->None] == Divide[1,Sqrt[1 - 6*x + (x)^(2)]]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E7 n = 0 M ( n ) x n = 1 - x - 1 - 2 x - 3 x 2 2 x 2 superscript subscript 𝑛 0 𝑀 𝑛 superscript 𝑥 𝑛 1 𝑥 1 2 𝑥 3 superscript 𝑥 2 2 superscript 𝑥 2 {\displaystyle{\displaystyle\sum_{n=0}^{\infty}M(n)x^{n}=\frac{1-x-\sqrt{1-2x-% 3x^{2}}}{2x^{2}}}}
\sum_{n=0}^{\infty}M(n)x^{n} = \frac{1-x-\sqrt{1-2x-3x^{2}}}{2x^{2}}

sum((sum(((- 1)^(k))/(n + 2 - k)*binomial(n,k)*binomial(2*n + 2 - 2*k,n + 1 - k), k = 0..n))*(x)^(n), n = 0..infinity) = (1 - x -sqrt(1 - 2*x - 3*(x)^(2)))/(2*(x)^(2))
Sum[(Sum[Divide[(- 1)^(k),n + 2 - k]*Binomial[n,k]*Binomial[2*n + 2 - 2*k,n + 1 - k], {k, 0, n}, GenerateConditions->None])*(x)^(n), {n, 0, Infinity}, GenerateConditions->None] == Divide[1 - x -Sqrt[1 - 2*x - 3*(x)^(2)],2*(x)^(2)]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E8 n , k = 1 N ( n , k ) x n y k = 1 - x - x y - ( 1 - x - x y ) 2 - 4 x 2 y 2 x superscript subscript 𝑛 𝑘 1 𝑁 𝑛 𝑘 superscript 𝑥 𝑛 superscript 𝑦 𝑘 1 𝑥 𝑥 𝑦 superscript 1 𝑥 𝑥 𝑦 2 4 superscript 𝑥 2 𝑦 2 𝑥 {\displaystyle{\displaystyle\sum_{n,k=1}^{\infty}N(n,k)x^{n}y^{k}=\frac{1-x-xy% -\sqrt{(1-x-xy)^{2}-4x^{2}y}}{2x}}}
\sum_{n,k=1}^{\infty}N(n,k)x^{n}y^{k} = \frac{1-x-xy-\sqrt{(1-x-xy)^{2}-4x^{2}y}}{2x}

sum(sum(((1)/(n)*binomial(n,k)*binomial(n,k - 1))*(x)^(n)* (y)^(k), k = 1..infinity), n = 1..infinity) = (1 - x - x*y -sqrt((1 - x - x*y)^(2)- 4*(x)^(2)* y))/(2*x)
Sum[Sum[(Divide[1,n]*Binomial[n,k]*Binomial[n,k - 1])*(x)^(n)* (y)^(k), {k, 1, Infinity}, GenerateConditions->None], {n, 1, Infinity}, GenerateConditions->None] == Divide[1 - x - x*y -Sqrt[(1 - x - x*y)^(2)- 4*(x)^(2)* y],2*x]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E9 n = 0 r ( n ) x n = 1 - x - 1 - 6 x + x 2 2 x superscript subscript 𝑛 0 𝑟 𝑛 superscript 𝑥 𝑛 1 𝑥 1 6 𝑥 superscript 𝑥 2 2 𝑥 {\displaystyle{\displaystyle\sum_{n=0}^{\infty}r(n)x^{n}=\frac{1-x-\sqrt{1-6x+% x^{2}}}{2x}}}
\sum_{n=0}^{\infty}r(n)x^{n} = \frac{1-x-\sqrt{1-6x+x^{2}}}{2x}
n 1 𝑛 1 {\displaystyle{\displaystyle n\geq 1}}
sum((D(n , n)- D(n + 1 , n - 1))*(x)^(n), n = 0..infinity) = (1 - x -sqrt(1 - 6*x + (x)^(2)))/(2*x)
Sum[(D[n , n]- D[n + 1 , n - 1])*(x)^(n), {n, 0, Infinity}, GenerateConditions->None] == Divide[1 - x -Sqrt[1 - 6*x + (x)^(2)],2*x]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E10 D ( m , n ) = D ( m , n - 1 ) + D ( m - 1 , n ) + D ( m - 1 , n - 1 ) 𝐷 𝑚 𝑛 𝐷 𝑚 𝑛 1 𝐷 𝑚 1 𝑛 𝐷 𝑚 1 𝑛 1 {\displaystyle{\displaystyle D(m,n)=D(m,n-1)+D(m-1,n)+D(m-1,n-1)}}
D(m,n) = D(m,n-1)+D(m-1,n)+D(m-1,n-1)
m 1 , n 1 formulae-sequence 𝑚 1 𝑛 1 {\displaystyle{\displaystyle m\geq 1,n\geq 1}}
(sum(binomial(n,k)*binomial(m + n - k,n), k = 0..n)) = D(m , n - 1)+ D(m - 1 , n)+ D(m - 1 , n - 1)
(Sum[Binomial[n,k]*Binomial[m + n - k,n], {k, 0, n}, GenerateConditions->None]) == D[m , n - 1]+ D[m - 1 , n]+ D[m - 1 , n - 1]
Skipped - no semantic math Skipped - no semantic math - -
26.6.E11 M ( n ) = M ( n - 1 ) + k = 2 n M ( k - 2 ) M ( n - k ) 𝑀 𝑛 𝑀 𝑛 1 superscript subscript 𝑘 2 𝑛 𝑀 𝑘 2 𝑀 𝑛 𝑘 {\displaystyle{\displaystyle M(n)=M(n-1)+\sum_{k=2}^{n}M(k-2)\,M(n-k)}}
M(n) = M(n-1)+\sum_{k=2}^{n}M(k-2)\,M(n-k)
n 2 𝑛 2 {\displaystyle{\displaystyle n\geq 2}}
(sum(((- 1)^(k))/(n + 2 - k)*binomial(n,k)*binomial(2*n + 2 - 2*k,n + 1 - k), k = 0..n)) = M*(n - 1)+ sum(M*(k - 2)*M*(n - k), k = 2..n)
(Sum[Divide[(- 1)^(k),n + 2 - k]*Binomial[n,k]*Binomial[2*n + 2 - 2*k,n + 1 - k], {k, 0, n}, GenerateConditions->None]) == M*(n - 1)+ Sum[M*(k - 2)*M*(n - k), {k, 2, n}, GenerateConditions->None]
Skipped - no semantic math Skipped - no semantic math - -